Electrospun Medicated Nanofibers for Wound Healing: Review - Xinkuan Liu; Haixia Xu; Mingxin Zhang; Deng-Guang Yu (Membranes, 2021)
With the increasing demand for wound care and treatment worldwide, traditional dressings have been unable to meet the needs of the existing market due to their limited antibacterial properties and other defects. Electrospinning technology has attracted more and more researchers’ attention as a simple and versatile manufacturing method. The electrospun nanofiber membrane has a unique structure and biological function similar to the extracellular matrix (ECM), and is considered an advanced wound dressing. They have significant potential in encapsulating and delivering active substances that promote wound healing. This article first discusses the common types of wound dressing, and then summarizes the development of electrospun fiber preparation technology. Finally, the polymers and common biologically active substances used in electrospinning wound dressings are summarized, and portable electrospinning equipment is also discussed. Additionally, future research needs are put forward.